Liddle′s Syndrome Case Report-Unusual Presentation with Hypertension in Children (Archives of Clinical and Medical Case Reports, 2018)
Increased blood pressure in children is usually secondary to a known cause. It is very important to discover the cause of high blood pressure, to treat it before the development of complications, and to prevent morbidity and mortality at this age. In this article, we will present a case of a 10-years-old girl with increased blood pressure and hypokalemia, we have been excluded any other causes for the high blood pressure, and after a favorable response to appropriate treatment, Amiloride, with a supportive laboratory, she was diagnosed with Liddle Syndrome.